A Randomized Clinical Trial on Acupuncture Versus Best Medical Therapy in Episodic Migraine Prophylaxis: The ACUMIGRAN Study - Giannini, Giulia; Favoni, Valentina; Merli, Elena; Nicodemo, Marianna; Torelli, Paola; Matrà, Annunzio; Giovanardi, Carlo Maria; Cortelli, Pietro; Pierangeli, Giulia; Cevoli, Sabina (Frontiers in Neurology, 2021)
Introduction: A large corpus of evidence has reported encouraging results for acupuncture as a prophylaxis therapy for migraine. However, trials that investigated the efficacy of acupuncture in comparison with pharmacological treatment in episodic migraine showed conflicting results. The study aimed to evaluate if acupuncture is as effective as evidence-based pharmacological drugs in episodic migraine prophylaxis. Methods: This is a randomized controlled clinical study. Patients suffering from migraine without preventive treatment in the past 3 months were recruited. After the run-in period, episodic migraineurs were assigned randomly to two groups: the acupuncture group (A) was treated with 12 sessions of acupuncture, and the pharmacological group (B) was treated with the most appropriate medication for each patient. Headache frequency was compared at baseline and at the end of treatment. Both groups were evaluated 3 and 6 months after treatment. Results: A total of 148 patients (24 males and 124 females) were enrolled in the study. Out of these, 69 were randomized to A and 66 to B. At baseline, no significant differences were found between the two groups. Of the patients, 15.5% (21/135) interrupted the treatment, especially those randomized to B. After 4 months, migraine frequency decreased from 8.58 ± 3.21 to 6.43 ± 3.45 in A and from 8.29 ± 2.72 to 6.27 ± 4.01 in B. Headache frequency decreased significantly after treatment without differences between the two groups (time-effect: p < 0.001; group effect: p = 0.332; interaction time-group effects: p = 0.556). Approximately 34% of patients showed a reduction of headache days by at least 50% after the treatment. The improvements observed at the end of treatment persisted in 57.3% (59/103) after 3 months and 38.8% (40/103) after 6 months, especially in patients randomized to A. Conclusions: Our trial is the first one comparing acupuncture with the more appropriate pharmacological treatment for migraine prophylaxis. Data suggested that acupuncture could be adopted as migraine prophylaxis and seem to be slightly superior to pharmacological treatment in compliance and rate of adverse events.